A high performance unsaturated polyester resin
Based on the combination of modified diatom soil and flame retardant monomers with the cross -linking monomer, high -performance unsaturated polyester resin is formed, which solves the problem of migration of the existing low molecular flame retardant in the existing flame retardant resin, and realizes more stable performance. And better environmental adaptability.
Patent Information
- Application Number
- CN202411614494.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
During the use or storage of existing flame retardant unsaturated polyester resins, low-molecular flame retardants may migrate, resulting in poor performance and may cause environmental pollution.
By mixing the diatomic soil and silver nitrate solution, obtained silver diatomic soil, and reacts with 3-amino propionide trimethyloxane, 3-hydrophiline popthyde, etc. Body, combined with cross -linking monomers to form a high -performance unsaturated polyester resin.
It improves the antibacterial, aging and mechanical properties of high -performance unsaturated polyester resin, while enhancing its flame retardability and self -repairing performance.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyester resins, in particular to a high-performance unsaturated polyester resin. Background Art
[0002] Unsaturated polyester resin is one of the most widely used thermosetting resins. It has excellent machinability, heat resistance and chemical corrosion resistance, and is mainly used in aerospace, automobile, construction, coating, electronic appliances and other fields. The flame-retardant unsaturated polyester resin products currently sold on the market basically use additive flame retardants. During the preparation process, the flame retardant is evenly dispersed in the resin matrix by a simple mechanical mixing method. There is no chemical bond between the flame retardant and the resin matrix, so the compatibility between the two is not good, resulting in the deterioration of the comprehensive performance of the flame retardant material. And with the increase of use or storage time, low molecular weight flame retardants may also slowly migrate out of the resin matrix under the action of heat or solvent, thereby deteriorating the performance of the product and may also cause environmental pollution. Therefore, the present invention prepares a high-performance unsaturated polyester resin with excellent flame retardancy. Summary of the invention
[0003] The purpose of the present invention is to provide a high-performance unsaturated polyester resin to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A high-performance unsaturated polyester resin is obtained by uniformly mixing modified unsaturated polyester resin, modified diatomaceous earth and a cross-linking monomer.
[0006] As an optimization, the modified unsaturated polyester resin is obtained by reacting 2-formyl pyridine and 3-aminopropane phosphoric acid, and then copolymerizing with terephthalic acid, fumaric acid and 1,3-propylene glycol.
[0007] As an optimization, the modified diatomaceous earth is obtained by mixing diatomaceous earth and silver nitrate solution, and then reacting with 3-aminopropyltrimethoxysilane and 3-allyl salicylaldehyde in sequence.
[0008] As an optimization, the diatomaceous earth comes from Yongshun Mineral Products Processing Plant in Lingshou County.
[0009] As an optimization, the cross-linking monomer is obtained by reacting tris(dimethylaminopropyl)amine and 3-chloropropylene.
[0010] A high-performance unsaturated polyester resin comprises the following preparation steps:
[0011] (1) Mix the silver-loaded diatomite and anhydrous ethanol in a mass ratio of 1:(15-25), stir at 20-30°C and 100-200 rpm for 5-15 min, ultrasonically disperse for 2-4 min, add 3-aminopropyltrimethoxysilane (0.5-0.7 times the mass of the silver-loaded diatomite), adjust the pH to 5-7 with 35%-37% acetic acid solution, heat to 35-45°C, continue stirring for 23-25 h, filter, and wash with deionized water for 3-5 min. The pre-modified diatomite was mixed with 3-allyl salicylaldehyde and anhydrous ethanol in a mass ratio of 1:(1.9-2.1):(10-20) for 20-40 minutes, stirred at 45-55°C and 100-200 rpm for 4-6 hours, and rotary evaporated at 50-60°C for 1-2 hours, washed with deionized water for 3-5 times, and dried at 65-75°C for 6-8 hours to obtain modified diatomite.
[0012] (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed in a mass ratio of 1:(37-38), stirred at 20-30°C and 100-300 rpm for 4-6 min, 3-chloropropylene (1.1-1.3 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate within 1-2 h, the temperature was raised to 135-145°C, stirring was continued for 7-9 h, naturally cooled to room temperature, and rotary evaporated at 50-60°C for 1-2 h to obtain a cross-linking monomer;
[0013] (3) 2-formylpyridine, 3-aminopropanephosphoric acid and anhydrous ethanol are mixed in a mass ratio of 1:(1.2-1.4):(20-30), stirred at 45-55°C and 100-200 rpm for 8-10 hours, rotary evaporated for 1-2 hours, washed with deionized water for 3-5 times, and dried at 55-65°C for 11-13 hours to obtain a flame retardant monomer;
[0014] (4) Mix terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide in a mass ratio of 1:(0.6~0.8):(1.1~1.2):(0.01~0.02), heat to 200~210℃ at a rate of 10~20℃ / min in a nitrogen atmosphere, stir at 200~300rpm for 45~55min, cool to 115~125℃, add flame retardant monomer (0.6~0.7 times the mass of terephthalic acid), heat to 200~210℃ and continue stirring. Continue stirring for 0.5~1.5h, cool to 95~105℃ and continue stirring for 25~35min to obtain modified unsaturated polyester resin; mix the modified unsaturated polyester resin, modified diatomaceous earth and cross-linking monomer in a mass ratio of 1:(0.07~0.08):(0.3~0.5), stir at 95~105℃ and 100~200rpm for 10~20min, cool to 80~90℃, continue stirring for 15~25min, and naturally cool to room temperature to obtain high-performance unsaturated polyester resin.
[0015] As an optimization, the silver-loaded diatomaceous earth in step (1) is obtained by mixing diatomaceous earth and 0.1 mol / L silver nitrate solution in a mass ratio of 1:10, stirring at 25°C and 250 rpm in the dark for 2 hours, vacuum impregnating for 30 minutes, filtering, washing with deionized water 4 times, and drying at 70°C for 8 hours.
[0016] As an optimization, the reaction equation of the pre-modified diatomaceous earth in step (1) is:
[0017] ;
[0018] Dia is the abbreviation of diatomaceous earth.
[0019] As an optimization, the reaction equation of the modified diatomaceous earth in step (1) is:
[0020] ;
[0021] Dia is the abbreviation of diatomaceous earth.
[0022] As an optimization, the reaction equation of the cross-linking monomer in step (2) is:
[0023] .
[0024] As an optimization, the reaction equation of the flame retardant monomer in step (3) is:
[0025] .
[0026] As an optimization, the reaction equation of the modified unsaturated polyester resin in step (4) is:
[0027] .
[0028] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0029] When preparing the high-performance unsaturated polyester resin, the present invention comprises the following steps: mixing diatomite and silver nitrate solution to obtain silver-loaded diatomite; reacting the silver-loaded diatomite with 3-aminopropyltrimethoxysilane and 3-allyl salicylaldehyde in sequence to obtain modified diatomite; reacting tris(dimethylaminopropyl)amine with 3-chloropropylene to obtain a crosslinking monomer; reacting 2-formylpyridine with 3-aminopropanephosphoric acid to obtain a flame retardant monomer; reacting terephthalic acid, fumaric acid, 1,3-propylene glycol with the flame retardant monomer to obtain a modified unsaturated polyester resin; and mixing the modified unsaturated polyester resin, the modified diatomite and the crosslinking monomer to obtain a high-performance unsaturated polyester resin.
[0030] First, diatomaceous earth and silver nitrate solution are mixed to obtain silver-loaded diatomaceous earth; then, the silver-loaded diatomaceous earth is reacted with 3-aminopropyltrimethoxysilane and 3-allyl salicylaldehyde in sequence to obtain modified diatomaceous earth; tri(dimethylaminopropyl)amine and 3-chloropropylene are reacted to obtain a cross-linking monomer; utilizing the adsorption characteristics of diatomaceous earth, a large amount of silver ions are loaded through a vacuum impregnation method, cell walls and cell membranes of bacteria are destroyed, bacterial metabolism and reproduction are affected, and the antibacterial property of high-performance unsaturated polyester resin is improved; 3-allyl salicylaldehyde is grafted through a Schiff base reaction to form a hydrogen bond hexacyclic ring, which is opened after absorbing energy under ultraviolet irradiation, and can convert harmful energy into harmless light waves or heat energy release, thereby improving the anti-aging property of high-performance unsaturated polyester resin; at the same time, the carbon-carbon double bond on 3-allyl salicylaldehyde can participate in the curing and cross-linking of the resin, thereby improving the dispersibility of diatomaceous earth, enriching the cross-linking network, and improving the mechanical properties of high-performance unsaturated polyester resin.
[0031] Secondly, tri(dimethylaminopropyl)amine and 3-chloropropylene are reacted to obtain a crosslinking monomer; 2-formylpyridine and 3-aminopropane phosphate are reacted to obtain a flame retardant monomer; terephthalic acid, fumaric acid, 1,3-propylene glycol and the flame retardant monomer are reacted to obtain a modified unsaturated polyester resin; the modified unsaturated polyester resin, modified diatomaceous earth and the crosslinking monomer are mixed to obtain a high-performance unsaturated polyester resin; a multi-double bond crosslinking monomer is synthesized by a quaternization reaction to promote the formation of a three-dimensional network structure between the polyester resin main body and form an ion molecular layer, and charge, thereby improving the antistatic properties of high-performance unsaturated polyester resins; utilizing the Schiff base reaction to synthesize flame-retardant monomers to participate in the polymerization of the polyester resin main chain, introducing the phosphorus element, and generating substances that can react with hydrogen and free radicals in the combustion products under high temperature conditions, thereby improving the flame retardancy of high-performance unsaturated polyester resins; at the same time, the pyridine Schiff base structure in the flame retardant monomer can complex metal ions to form a dynamic covalent five-membered ring structure, enriching the bonding force between the polyester main body and diatomaceous earth and the metal matrix, thereby improving the self-healing properties of high-performance unsaturated polyester resins. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] Embodiment 1:
[0034] A high-performance unsaturated polyester resin, the high-performance unsaturated polyester resin comprising the following preparation steps:
[0035] (1) The silver-loaded diatomite and anhydrous ethanol were mixed in a mass ratio of 1:15, stirred at 20°C and 100 rpm for 15 minutes, ultrasonically dispersed for 4 minutes, 3-aminopropyltrimethoxysilane was added in an amount of 0.5 times the mass of the silver-loaded diatomite, the pH was adjusted to 5 with a 35% mass fraction of acetic acid solution, the temperature was raised to 35°C and stirred for 25 hours, then filtered, washed with deionized water for 3 times, and dried at 60°C for 10 hours to obtain pre-modified diatomite; the pre-modified diatomite, 3-allyl salicylaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:1.9:10, ultrasonically dispersed for 20 minutes, stirred at 45°C and 100 rpm for 6 hours, rotary evaporated at 50°C for 2 hours, washed with deionized water for 3 times, and dried at 65°C for 8 hours to obtain modified diatomite;
[0036] (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed at a mass ratio of 1:37, stirred at 20°C and 100 rpm for 6 min, 3-chloropropylene (1.1 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate within 1 h, the temperature was raised to 135°C, stirring was continued for 9 h, naturally cooled to room temperature, and rotary evaporated at 50°C for 2 h to obtain a cross-linking monomer;
[0037] (3) 2-formylpyridine, 3-aminopropanephosphoric acid and anhydrous ethanol were mixed in a mass ratio of 1:1.2:20, stirred at 45°C and 100 rpm for 10 h, rotary evaporated for 1 h, washed with deionized water three times, and dried at 55°C for 13 h to obtain a flame retardant monomer;
[0038] (4) Terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide were mixed in a mass ratio of 1:0.6:1.1:0.01, heated to 200°C at a rate of 10°C / min in a nitrogen atmosphere, stirred at 200 rpm for 55 min, cooled to 115°C, added with a flame retardant monomer in an amount of 0.6 times the mass of terephthalic acid, heated to 200°C and continued to stir for 1.5 h, cooled to 95°C and continued to stir for 35 min, to obtain a modified unsaturated polyester resin; the modified unsaturated polyester resin, modified diatomaceous earth and a cross-linking monomer were mixed in a mass ratio of 1:0.07:0.3, stirred at 95°C and 100 rpm for 20 min, cooled to 80°C, continued to stir for 25 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
[0039] Embodiment 2:
[0040] A high-performance unsaturated polyester resin, the high-performance unsaturated polyester resin comprising the following preparation steps:
[0041] (1) The silver-loaded diatomite and anhydrous ethanol were mixed in a mass ratio of 1:20, stirred at 25°C and 150 rpm for 10 min, ultrasonically dispersed for 3 min, 0.6 times the mass of the silver-loaded diatomite was added with 3-aminopropyltrimethoxysilane, the pH was adjusted to 6 with a mass fraction of 36% acetic acid solution, the temperature was raised to 40°C and stirred for 24 h, then filtered, washed with deionized water for 4 times, and dried at 65°C for 9 h to obtain pre-modified diatomite; the pre-modified diatomite, 3-allyl salicylaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:2:15, ultrasonically dispersed for 30 min, stirred at 50°C and 150 rpm for 5 h, rotary evaporated at 55°C for 1.5 h, washed with deionized water for 4 times, and dried at 70°C for 7 h to obtain modified diatomite;
[0042] (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed at a mass ratio of 1:37.5, stirred at 25°C and 200 rpm for 5 min, 3-chloropropylene (1.2 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate over 1.5 h, the temperature was raised to 140°C, stirring was continued for 8 h, naturally cooled to room temperature, and rotary evaporated at 55°C for 1.5 h to obtain a cross-linking monomer;
[0043] (3) 2-formylpyridine, 3-aminopropanephosphoric acid and anhydrous ethanol were mixed in a mass ratio of 1:1.3:25, stirred at 50°C and 150 rpm for 9 hours, rotary evaporated for 1.5 hours, washed with deionized water 4 times, and dried at 60°C for 12 hours to obtain a flame retardant monomer;
[0044] (4) Terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide were mixed in a mass ratio of 1:0.7:1.15:0.015, heated to 205°C at a rate of 15°C / min in a nitrogen atmosphere, stirred at 250 rpm for 50 min, cooled to 120°C, added with a flame retardant monomer in an amount of 0.65 times the mass of terephthalic acid, heated to 205°C and continued to stir for 1 h, cooled to 100°C and continued to stir for 30 min, to obtain a modified unsaturated polyester resin; the modified unsaturated polyester resin, modified diatomaceous earth and a cross-linking monomer were mixed in a mass ratio of 1:0.075:0.4, stirred at 100°C and 150 rpm for 15 min, cooled to 85°C, continued to stir for 20 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
[0045] Embodiment 3:
[0046] A high-performance unsaturated polyester resin, the high-performance unsaturated polyester resin comprising the following preparation steps:
[0047] (1) Silver-loaded diatomite and anhydrous ethanol were mixed in a mass ratio of 1:25, stirred at 30°C and 200 rpm for 5 min, ultrasonically dispersed for 2 min, 3-aminopropyltrimethoxysilane (0.7 times the mass of the silver-loaded diatomite) was added, the pH was adjusted to 7 with a 37% mass fraction of acetic acid solution, the temperature was raised to 45°C and stirred for 23 h, then filtered, washed with deionized water for 5 times, and dried at 70°C for 8 h to obtain pre-modified diatomite; pre-modified diatomite, 3-allyl salicylaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:2.1:20, ultrasonically dispersed for 40 min, stirred at 55°C and 200 rpm for 4 h, rotary evaporated at 60°C for 1 h, washed with deionized water for 5 times, and dried at 75°C for 6 h to obtain modified diatomite;
[0048] (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed at a mass ratio of 1:38, stirred at 30°C and 300 rpm for 4 min, 3-chloropropylene (1.3 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate over 2 h, the temperature was raised to 145°C, stirring was continued for 7 h, naturally cooled to room temperature, and rotary evaporated at 60°C for 1 h to obtain a cross-linking monomer;
[0049] (3) 2-formylpyridine, 3-aminopropanephosphoric acid and anhydrous ethanol were mixed in a mass ratio of 1:1.4:30, stirred at 55°C and 200 rpm for 8 h, rotary evaporated for 2 h, washed with deionized water 5 times, and dried at 65°C for 11 h to obtain a flame retardant monomer;
[0050] (4) Terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide were mixed in a mass ratio of 1:0.8:1.2:0.02, heated to 210°C at a rate of 20°C / min in a nitrogen atmosphere, stirred at 300 rpm for 45 min, cooled to 125°C, added with a flame retardant monomer in an amount of 0.7 times the mass of terephthalic acid, heated to 210°C and continued to stir for 0.5 h, cooled to 105°C and continued to stir for 25 min, to obtain a modified unsaturated polyester resin; the modified unsaturated polyester resin, modified diatomaceous earth and a cross-linking monomer were mixed in a mass ratio of 1:0.08:0.5, stirred at 105°C and 200 rpm for 10 min, cooled to 90°C, continued to stir for 15 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
[0051] Comparative Example 1:
[0052] A high-performance unsaturated polyester resin, the high-performance unsaturated polyester resin comprising the following preparation steps:
[0053] (1) Silver-loaded diatomite and anhydrous ethanol were mixed in a mass ratio of 1:20, stirred at 25°C and 150 rpm for 10 min, ultrasonically dispersed for 3 min, 3-aminopropyltrimethoxysilane (0.6 times the mass of the silver-loaded diatomite) was added, the pH was adjusted to 6 with a 36% acetic acid solution, the temperature was raised to 40°C, stirring was continued for 24 h, and then filtered, washed with deionized water 4 times, and dried at 65°C for 9 h to obtain pre-modified diatomite;
[0054] (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed at a mass ratio of 1:37.5, stirred at 25°C and 200 rpm for 5 min, 3-chloropropylene (1.2 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate over 1.5 h, the temperature was raised to 140°C, stirring was continued for 8 h, naturally cooled to room temperature, and rotary evaporated at 55°C for 1.5 h to obtain a cross-linking monomer;
[0055] (3) 2-formylpyridine, 3-aminopropanephosphoric acid and anhydrous ethanol were mixed in a mass ratio of 1:1.3:25, stirred at 50°C and 150 rpm for 9 hours, rotary evaporated for 1.5 hours, washed with deionized water 4 times, and dried at 60°C for 12 hours to obtain a flame retardant monomer;
[0056] (4) Terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide were mixed in a mass ratio of 1:0.7:1.15:0.015, heated to 205°C at a rate of 15°C / min in a nitrogen atmosphere, stirred at 250 rpm for 50 min, cooled to 120°C, added with a flame retardant monomer in an amount of 0.65 times the mass of terephthalic acid, heated to 205°C and continued to stir for 1 h, cooled to 100°C and continued to stir for 30 min, to obtain a modified unsaturated polyester resin; the modified unsaturated polyester resin, pre-modified diatomaceous earth and cross-linking monomer were mixed in a mass ratio of 1:0.075:0.4, stirred at 100°C and 150 rpm for 15 min, cooled to 85°C, continued to stir for 20 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
[0057] Comparative Example 2:
[0058] A high-performance unsaturated polyester resin, the high-performance unsaturated polyester resin comprising the following preparation steps:
[0059] (1) Mix diatomite and anhydrous ethanol in a mass ratio of 1:20, stir at 25°C and 150 rpm for 10 min, ultrasonically disperse for 3 min, add 3-aminopropyltrimethoxysilane in an amount of 0.6 times the mass of diatomite, adjust the pH to 6 with a 36% mass fraction acetic acid solution, heat to 40°C and continue stirring for 24 h, filter, wash with deionized water 4 times, and dry at 65°C for 9 h to obtain pre-modified diatomite; mix pre-modified diatomite, 3-allyl salicylaldehyde and anhydrous ethanol in a mass ratio of 1:2:15, ultrasonically disperse for 30 min, stir at 50°C and 150 rpm for 5 h, rotary evaporate at 55°C for 1.5 h, wash with deionized water 4 times, and dry at 70°C for 7 h to obtain modified diatomite;
[0060] (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed at a mass ratio of 1:37.5, stirred at 25°C and 200 rpm for 5 min, 3-chloropropylene (1.2 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate over 1.5 h, the temperature was raised to 140°C, stirring was continued for 8 h, naturally cooled to room temperature, and rotary evaporated at 55°C for 1.5 h to obtain a cross-linking monomer;
[0061] (3) 2-formylpyridine, 3-aminopropanephosphoric acid and anhydrous ethanol were mixed in a mass ratio of 1:1.3:25, stirred at 50°C and 150 rpm for 9 hours, rotary evaporated for 1.5 hours, washed with deionized water 4 times, and dried at 60°C for 12 hours to obtain a flame retardant monomer;
[0062] (4) Terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide were mixed in a mass ratio of 1:0.7:1.15:0.015, heated to 205°C at a rate of 15°C / min in a nitrogen atmosphere, stirred at 250 rpm for 50 min, cooled to 120°C, added with a flame retardant monomer in an amount of 0.65 times the mass of terephthalic acid, heated to 205°C and continued to stir for 1 h, cooled to 100°C and continued to stir for 30 min, to obtain a modified unsaturated polyester resin; the modified unsaturated polyester resin, modified diatomaceous earth and a cross-linking monomer were mixed in a mass ratio of 1:0.075:0.4, stirred at 100°C and 150 rpm for 15 min, cooled to 85°C, continued to stir for 20 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
[0063] Comparative Example 3:
[0064] A high-performance unsaturated polyester resin, the high-performance unsaturated polyester resin comprising the following preparation steps:
[0065] (1) The silver-loaded diatomite and anhydrous ethanol were mixed in a mass ratio of 1:20, stirred at 25°C and 150 rpm for 10 min, ultrasonically dispersed for 3 min, 0.6 times the mass of the silver-loaded diatomite was added with 3-aminopropyltrimethoxysilane, the pH was adjusted to 6 with a mass fraction of 36% acetic acid solution, the temperature was raised to 40°C and stirred for 24 h, then filtered, washed with deionized water for 4 times, and dried at 65°C for 9 h to obtain pre-modified diatomite; the pre-modified diatomite, 3-allyl salicylaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:2:15, ultrasonically dispersed for 30 min, stirred at 50°C and 150 rpm for 5 h, rotary evaporated at 55°C for 1.5 h, washed with deionized water for 4 times, and dried at 70°C for 7 h to obtain modified diatomite;
[0066] (2) 2-formylpyridine, 3-aminopropanephosphoric acid and anhydrous ethanol were mixed in a mass ratio of 1:1.3:25, stirred at 50°C and 150 rpm for 9 hours, rotary evaporated for 1.5 hours, washed with deionized water 4 times, and dried at 60°C for 12 hours to obtain a flame retardant monomer;
[0067] (3) Terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide were mixed in a mass ratio of 1:0.7:1.15:0.015, and the mixture was heated to 205°C at a rate of 15°C / min in a nitrogen atmosphere, stirred at 250 rpm for 50 min, cooled to 120°C, and a flame retardant monomer (0.65 times the mass of terephthalic acid) was added, the mixture was heated to 205°C and stirred for 1 h, cooled to 100°C and stirred for 30 min to obtain a modified unsaturated polyester resin; the modified unsaturated polyester resin, modified diatomaceous earth and styrene were mixed in a mass ratio of 1:0.075:0.4, stirred at 100°C and 150 rpm for 15 min, cooled to 85°C, stirred for 20 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
[0068] Comparative Example 4:
[0069] A high-performance unsaturated polyester resin, the high-performance unsaturated polyester resin comprising the following preparation steps:
[0070] (1) The silver-loaded diatomite and anhydrous ethanol were mixed in a mass ratio of 1:20, stirred at 25°C and 150 rpm for 10 min, ultrasonically dispersed for 3 min, 0.6 times the mass of the silver-loaded diatomite was added with 3-aminopropyltrimethoxysilane, the pH was adjusted to 6 with a mass fraction of 36% acetic acid solution, the temperature was raised to 40°C and stirred for 24 h, then filtered, washed with deionized water for 4 times, and dried at 65°C for 9 h to obtain pre-modified diatomite; the pre-modified diatomite, 3-allyl salicylaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:2:15, ultrasonically dispersed for 30 min, stirred at 50°C and 150 rpm for 5 h, rotary evaporated at 55°C for 1.5 h, washed with deionized water for 4 times, and dried at 70°C for 7 h to obtain modified diatomite;
[0071] (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed at a mass ratio of 1:37.5, stirred at 25°C and 200 rpm for 5 min, 3-chloropropylene (1.2 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate over 1.5 h, the temperature was raised to 140°C, stirring was continued for 8 h, naturally cooled to room temperature, and rotary evaporated at 55°C for 1.5 h to obtain a cross-linking monomer;
[0072] (3) Terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide were mixed in a mass ratio of 1:0.7:1.15:0.015, and the mixture was heated to 205°C at a rate of 15°C / min in a nitrogen atmosphere, stirred at 250 rpm for 50 min, cooled to 120°C, 3-aminopropane phosphoric acid (0.65 times the mass of terephthalic acid) was added, the mixture was heated to 205°C and stirred for 1 h, cooled to 100°C and stirred for 30 min to obtain a modified unsaturated polyester resin; the modified unsaturated polyester resin, modified diatomaceous earth and cross-linking monomer were mixed in a mass ratio of 1:0.075:0.4, stirred at 100°C and 150 rpm for 15 min, cooled to 85°C, stirred for 20 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
[0073] Comparative Example 5:
[0074] A high-performance unsaturated polyester resin, the high-performance unsaturated polyester resin comprising the following preparation steps:
[0075] (1) The silver-loaded diatomite and anhydrous ethanol were mixed in a mass ratio of 1:20, stirred at 25°C and 150 rpm for 10 min, ultrasonically dispersed for 3 min, 0.6 times the mass of the silver-loaded diatomite was added with 3-aminopropyltrimethoxysilane, the pH was adjusted to 6 with a mass fraction of 36% acetic acid solution, the temperature was raised to 40°C and stirred for 24 h, then filtered, washed with deionized water for 4 times, and dried at 65°C for 9 h to obtain pre-modified diatomite; the pre-modified diatomite, 3-allyl salicylaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:2:15, ultrasonically dispersed for 30 min, stirred at 50°C and 150 rpm for 5 h, rotary evaporated at 55°C for 1.5 h, washed with deionized water for 4 times, and dried at 70°C for 7 h to obtain modified diatomite;
[0076] (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed at a mass ratio of 1:37.5, stirred at 25°C and 200 rpm for 5 min, 3-chloropropylene (1.2 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate over 1.5 h, the temperature was raised to 140°C, stirring was continued for 8 h, naturally cooled to room temperature, and rotary evaporated at 55°C for 1.5 h to obtain a cross-linking monomer;
[0077] (3) Terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide were mixed in a mass ratio of 1:0.7:1.15:0.015, and the mixture was heated to 205°C at a rate of 15°C / min and stirred at 250 rpm for 50 min in a nitrogen atmosphere, then cooled to 120°C and stirred for 30 min to obtain an unsaturated polyester resin; unsaturated polyester resin, modified diatomaceous earth and cross-linking monomer were mixed in a mass ratio of 1:0.075:0.4, stirred at 100°C and 150 rpm for 15 min, cooled to 85°C, stirred for 20 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
[0078] Test Example 1:
[0079] High-performance unsaturated polyester resin, cobalt isooctanoate and methyl ethyl ketone peroxide were mixed in a mass ratio of 1:0.008:0.01, stirred at 300 rpm for 1 min, coated on the surface of a glass sheet to a thickness of 2 mm, and then left to stand at 25°C for 24 h before peeling off to obtain a high-performance polyester resin film.
[0080] 1. Flame retardancy
[0081] Test method: Take samples of the high-performance polyester resin film obtained in each example and the comparative example with a size of 150 mm×58 mm×1 mm, and test the limiting oxygen index value using a JF-3 limiting oxygen index instrument.
[0082] 2. Antibacterial
[0083] Test method: Take samples of the same size as those of the high-performance polyester resin films obtained in each embodiment and the comparative example respectively, and mix 200 μL of a 1×10 -7 Escherichia coli liquid was dropped on the surface of the sample after UV sterilization, incubated for 1 hour and then rinsed. 20 μL of the eluate was taken and incubated in the culture medium for 48 hours. The number of colonies N was recorded, and the number of colonies in the blank group was M. The sterilization rate was calculated as (M–N) / M×100%.
[0084] 3. Antistatic
[0085] Test method: Take samples of the high-performance polyester resin film obtained in each embodiment and the comparative example with a size of 130 mm×100 mm, and test the surface resistivity using a surface resistance analyzer at 25° C. and an ambient humidity of 55%.
[0086] Table 1 below shows the analysis results of the flame retardant, antibacterial and antistatic properties of the high performance unsaturated polyester resins of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0087] Table 1
[0088] Limiting oxygen index% Sterilization rate% <![CDATA[Surface resistivity mΩ·cm 2 > Example 1 25.7 99.9 <![CDATA[2.5×10 8 ]]> Example 2 25.8 99.9 <![CDATA[2.4×10 8 ]]> Example 3 25.4 99.9 <![CDATA[2.8×10 8 ]]> Comparative Example 1 24.3 99.9 <![CDATA[3.2×10 8 ]]> Comparative Example 2 25.6 14.2 <![CDATA[2.9×10 8 ]]> Comparative Example 3 24.9 99.6 <![CDATA[1.7×10 12 ]]> Comparative Example 4 25.3 99.9 <![CDATA[3.1×10 8 ]]> Comparative Example 5 17.2 99.7 <![CDATA[3.4×10 8 ]]>
[0089] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the high-performance unsaturated polyester resin prepared in the present invention has good flame retardant, antibacterial and antistatic properties.
[0090] By comparison, the sterilization rates of Examples 1, 2, and 3 are higher than those of Comparative Example 2, which indicates that the adsorption characteristics of diatomaceous earth are utilized to load a large amount of silver ions through the vacuum impregnation method, thereby destroying the cell walls and cell membranes of bacteria, affecting bacterial metabolism and reproduction, and improving the antibacterial properties of the high-performance unsaturated polyester resin.
[0091] By comparison, the surface resistivity of Examples 1, 2, and 3 is lower than that of Comparative Example 3, which indicates that the synthesis of multi-double bond cross-linking monomers through quaternization reaction promotes the formation of a three-dimensional network structure between the main bodies of the polyester resin, while forming an ion molecular layer, neutralizing the charge, and improving the antistatic properties of the high-performance unsaturated polyester resin.
[0092] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 5, which indicates that by utilizing the Schiff base reaction to synthesize flame-retardant monomers to participate in the polymerization of the polyester resin main chain, phosphorus is introduced to generate substances that can react with hydrogen and free radicals in the combustion products under high temperature conditions, thereby improving the flame retardancy of the high-performance unsaturated polyester resin.
[0093] Test Example 2:
[0094] 1. Anti-aging and self-repairing
[0095] Test method: The high-performance polyester resin films obtained in each embodiment and the comparative example were cut into dumbbell-shaped samples according to GB1040 standard, and the tensile strength σ0 was tested at a speed of 50 mm / min at 25°C using a CMT4204 universal tensile testing machine; in an ultraviolet aging test box, a UV aging lamp (λ=365-400nm) was used to irradiate for 1 day when the surface temperature of the bulb reached 70°C, and the tensile strength σ1 was measured; the aging rate was calculated as (σ0-σ1) / σ0×100%; the dumbbell-shaped sample was cut in the middle, the cut surface was placed in close contact at 40°C for 4 hours, the tensile strength σ2 was measured, and the repair rate was calculated as σ2 / σ0×100%.
[0096] Table 2 below shows the analysis results of the anti-aging and self-repairing properties of the high-performance unsaturated polyester resins of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0097] Table 2
[0098] Aging rate% Repair rate% Aging rate% Repair rate% Example 1 10.2 86.3 Comparative Example 1 72.6 84.9 Example 2 9.8 87.1 Comparative Example 2 12.5 61.4 Example 3 10.5 86.7 Comparative Example 3 10.9 85.6 Comparative Example 4 11.7 14.2 Comparative Example 5 12.1 85.3
[0099] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the high-performance unsaturated polyester resin prepared in the present invention has good anti-aging and self-repairing properties.
[0100] By comparison, the aging rates of Examples 1, 2, and 3 are lower than those of Comparative Example 1, indicating that 3-allyl salicylaldehyde is grafted through the Schiff base reaction to form a hydrogen bonded six-membered ring, which absorbs energy after ultraviolet irradiation and opens, and can convert harmful energy into harmless light waves or heat energy release, thereby improving the aging resistance of the high-performance unsaturated polyester resin.
[0101] By comparison, the repair rates of Examples 1, 2, and 3 are higher than those of Comparative Example 4, indicating that the pyridine Schiff base structure in the flame retardant monomer can complex metal ions to form a dynamic covalent five-membered ring structure, enrich the binding force between the polyester body and diatomaceous earth and the metal matrix, and improve the self-healing properties of the high-performance unsaturated polyester resin.
[0102] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high performance unsaturated polyester resin, characterized in that: The high-performance unsaturated polyester resin is obtained by mixing modified unsaturated polyester resin, modified diatomaceous earth and a cross-linking monomer; The modified unsaturated polyester resin is obtained by reacting 2-formyl pyridine and 3-aminopropane phosphoric acid, and then copolymerizing with terephthalic acid, fumaric acid and 1,3-propylene glycol; The modified diatomaceous earth is obtained by mixing diatomaceous earth and silver nitrate solution, and then reacting with 3-aminopropyltrimethoxysilane and 3-allyl salicylaldehyde in sequence; The cross-linking monomer is obtained by reacting tris(dimethylaminopropyl)amine and 3-chloropropylene; The method comprises the following preparation steps: (1) Mix the silver-loaded diatomite and anhydrous ethanol in a mass ratio of 1:(15-25), stir at 20-30°C and 100-200 rpm for 5-15 min, ultrasonically disperse for 2-4 min, add 3-aminopropyltrimethoxysilane in an amount of 0.5-0.7 times the mass of the silver-loaded diatomite, adjust the pH to 5-7 with an acetic acid solution with a mass fraction of 35%-37%, heat to 35-45°C, continue stirring for 23-25 h, filter, wash with deionized water for 3-5 times, and dry at 60-70°C for 8-10 h to obtain pre-modified diatomite; Pre-modified diatomite, 3-allyl salicylaldehyde and anhydrous ethanol were mixed in a mass ratio of 1:(1.9-2.1):(10-20), ultrasonically dispersed for 20-40 min, stirred at 45-55° C. and 100-200 rpm for 4-6 h, rotary evaporated at 50-60° C. for 1-2 h, washed with deionized water for 3-5 times, and dried at 65-75° C. for 6-8 h to obtain modified diatomite; (2) Tris(dimethylaminopropyl)amine and anhydrous acetonitrile were mixed in a mass ratio of 1:(37-38), stirred at 20-30°C and 100-300 rpm for 4-6 min, 3-chloropropylene (1.1-1.3 times the mass of tris(dimethylaminopropyl)amine) was added at a uniform rate within 1-2 h, the temperature was raised to 135-145°C, stirring was continued for 7-9 h, naturally cooled to room temperature, and rotary evaporated at 50-60°C for 1-2 h to obtain a cross-linking monomer; (3) 2-formylpyridine, 3-aminopropanephosphoric acid and anhydrous ethanol are mixed in a mass ratio of 1:(1.2-1.4):(20-30), stirred at 45-55°C and 100-200 rpm for 8-10 hours, rotary evaporated for 1-2 hours, washed with deionized water for 3-5 times, and dried at 55-65°C for 11-13 hours to obtain a flame retardant monomer; (4) Mix terephthalic acid, fumaric acid, 1,3-propylene glycol and monobutyl tin oxide in a mass ratio of 1:(0.6-0.8):(1.1-1.2):(0.01-0.02), heat to 200-210°C at a rate of 10-20°C / min in a nitrogen atmosphere, stir at 200-300 rpm for 45-55 min, cool to 115-125°C, add a flame retardant monomer in an amount of 0.6-0.7 times the mass of terephthalic acid, heat to 200-210°C and continue stirring for 0.5-1.5 h, cool to 95-105°C and continue stirring for 25-35 min, to obtain a modified unsaturated polyester resin; The modified unsaturated polyester resin, modified diatomaceous earth and cross-linking monomer are mixed in a mass ratio of 1: (0.07-0.08): (0.3-0.5), stirred at 95-105°C and 100-200 rpm for 10-20 min, cooled to 80-90°C, continued to stir for 15-25 min, and naturally cooled to room temperature to obtain a high-performance unsaturated polyester resin.
2. A high performance unsaturated polyester resin according to claim 1, characterized in that: The silver-loaded diatomaceous earth in step (1) is prepared by mixing diatomaceous earth and 0.1 mol / L silver nitrate solution in a mass ratio of 1:10, stirring at 25° C. and 250 rpm in the dark for 2 h, vacuum impregnating for 30 min, filtering, washing with deionized water for 4 times, and drying at 70° C. for 8 h.
3. A high performance unsaturated polyester resin according to claim 1, characterized in that: The reaction equation of the pre-modified diatomaceous earth in step (1) is: ; Dia is the abbreviation of diatomaceous earth.
4. A high performance unsaturated polyester resin according to claim 1, characterized in that: The reaction equation of the modified diatomaceous earth in step (1) is: ; Dia is the abbreviation of diatomaceous earth.
5. A high performance unsaturated polyester resin according to claim 1, characterized in that: The reaction equation of the cross-linking monomer in step (2) is: 。 6. A high performance unsaturated polyester resin according to claim 1, characterized in that: The reaction equation of the flame retardant monomer in step (3) is: 。
Citation Information
Patent Citations
Metal coating composition
CN101918470A
Antibacterial waterproof high polymer material for tablecloth and preparation method of antibacterial waterproof high polymer material
CN118374135A